Reserve labor, unreserved politics: dignified encroachments under India's national rural employment guarantee act - Roy, I (Taylor and Francis, 2014)
The rural proletariat constitute a substantial proportion of the global poor. Leading better lives is central to their political practices. In this paper, I aim to elaborate the political practices that attend to these aspirations, interrogations and contests. I examine existing approaches to studying political practices of the rural proletariat. I do this with a focus on India, where the National Rural Employment Guarantee Act (NREGA) is in force since 2005. I locate the program against the backdrop of neoliberal transformations in India. I then examine the ways in which the rural proletariat engage with the program, even when other opportunities in the agricultural sector are available. Based on these examinations, I argue that the practices spawned by the program are to be understood as 'encroachments' into the extant social customs, norms and habits of rural India. This perspective, I contend, is more fruitful than locating the rural proletariat's engagement with the NREGA as a coping strategy or a tactic of resistance against rural elites. The data which this paper draws on include official sources, in-depth interviews with workers in rural Bihar and West Bengal and ethnographic observations. © 2014 Taylor and Francis.